The Effect of Argument-Driven Inquiry (ADI) Learning Model on Students' Mathematical Critical Thinking Skills - Astuti Handayani; Mara Samin Lubis (Universitas Negeri Makassar, 2024)
This research was carried out with the aim of finding out the effect of the Argument-Driven Inquiry Learning Model on students' mathematical thinking abilities at TNAS KARYA Batang Kuis Middle School for the 2023/2024 academic year. This research method is quantitative and the type of research is Quasi Experimental with the research design being Pretest-Posttest-Only Control Design. The data analysis technique in this research uses analysis prerequisite tests, namely: 1) Normality test, the results of the normality test produce a sig value. from the Pretest and Posttest data for the experimental and control classes is greater than 0.05, so the data is normally distributed, 2) Homogeneity test, the results of the homogeneity test for the Posttest data for the experimental class and control class are 0.479 and the sig. is greater than 0.05, then the variance of the two groups is homogeneous. 3) Hypothesis testing using the t test, the results of the t test show that the significant value (2 tailed) = 0.001 < 0.05. The significant value of the data is smaller than 0.05, so H0 is rejected. So it can be concluded that there is an influence of the Argument-Driven Inquiry learning model on students' mathematical critical thinking abilities.